2020
DOI: 10.1111/jcmm.14941
|View full text |Cite
|
Sign up to set email alerts
|

α5‐nAChR contributes to epithelial‐mesenchymal transition and metastasis by regulating Jab1/Csn5 signalling in lung cancer

Abstract: Recent studies have showed that α5 nicotinic acetylcholine receptor (α5‐nAChR) is closely associated with nicotine‐related lung cancer. Our previous studies also demonstrated that α5‐nAChR mediates nicotine‐induced lung carcinogenesis. However, the mechanism by which α5‐nAChR functions in lung carcinogenesis remains to be elucidated. Jab1/Csn5 is a key regulatory factor in smoking‐induced lung cancer. In this study, we explored the underlying mechanisms linking the α5‐nAChR‐Jab1/Csn5 axis with lung cancer epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
(100 reference statements)
3
17
0
Order By: Relevance
“…We demonstrated that α5-nAChR increased EGFR phosphorylation at Y1068, as well as the downstream signaling of EGFR such as STAT3 phosphorylation at Y705 and Akt phosphorylation at S473, which has been linked to cell survival and migration [44]. Consistently, a recent report also demonstrated the involvement of α5-nAChR in the EMT process and tumor metastasis through regulating the Jab1/Csn5 signaling in lung cancer [45]. Another study revealed the role of α5-nAChR in regulating cell proliferation and migration in melanoma cells [46].…”
Section: Discussionsupporting
confidence: 85%
“…We demonstrated that α5-nAChR increased EGFR phosphorylation at Y1068, as well as the downstream signaling of EGFR such as STAT3 phosphorylation at Y705 and Akt phosphorylation at S473, which has been linked to cell survival and migration [44]. Consistently, a recent report also demonstrated the involvement of α5-nAChR in the EMT process and tumor metastasis through regulating the Jab1/Csn5 signaling in lung cancer [45]. Another study revealed the role of α5-nAChR in regulating cell proliferation and migration in melanoma cells [46].…”
Section: Discussionsupporting
confidence: 85%
“…In humans, allelic variation in the α5 subunit reduces α4β2α5 nAChR function and is associated with an increased vulnerability for lung cancer ( Kuryatov et al, 2011 ; Li et al, 2011 ). Nicotine activation of α5-containing nAChRs in non-small cell lung cancer leads to downstream activation of several pathways that promote cancerous proliferation and metastasis, such as JAK2/STAT3, HIF-1α/VEGF and Jab1/Csn5, as demonstrated in vitro ( Chen et al, 2020a ; Ma et al, 2014 ; Sun and Ma, 2015 ; Sun et al, 2017 ; Zhang et al, 2017 ). Further, shRNA-mediated knockdown of the α5 nAChR subunit appears to inhibit lung tumor growth in vivo ( Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…As a downstream mechanism for α5 nAChR in nicotine-induced lung cancer, JAK2/STAT3 has been identified [ 94 ]. More recently it was also shown that Jab1/Csn5 expression was correlated with α5 nAChR expression in lung cancer and that it increased the expression of N-cadherin and vimentin, which is indicative for an induction of epithelial-mesenchymal transition [ 95 ]. Taken together, these studies show that inhibiting α5 nAChR might represent a promising target for therapy for nicotine-induced non-small cell lung cancer.…”
Section: The Role Of Nicotinic Acetylcholine Receptors In Lung Cancermentioning
confidence: 99%